2022
DOI: 10.3389/feduc.2022.822958
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning in Higher Education During Covid-19

Abstract: COVID-19’s pandemic has hastened the expansion of online learning across all levels of education. Countries have pushed to expand their use of distant education and make it mandatory in view of the danger of being unable to resume face-to-face education. The most frequently reported disadvantages are technological challenges and the resulting inability to open the system. Prior to the pandemic, interest in distance learning was burgeoning, as it was a unique style of instruction. The mini-review aims to ascert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 40 publications
0
31
0
4
Order By: Relevance
“…The results showed that the most important factors influencing students' feelings and convincing them to switch from classroom teaching to teaching in the distance learning model are the feeling of pleasure in distance education and a sense of self-efficacy. Masalimova et al (2022) studied students' attitudes toward distance education in COVID-19. They analyzed a total of 27 articles.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the most important factors influencing students' feelings and convincing them to switch from classroom teaching to teaching in the distance learning model are the feeling of pleasure in distance education and a sense of self-efficacy. Masalimova et al (2022) studied students' attitudes toward distance education in COVID-19. They analyzed a total of 27 articles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the onset of the COVID-19 pandemic, many studies have addressed the advantages and disadvantages of distance learning in higher education. However, few studies address the views of Russian higher education students (Masalimova et al, 2022). For this reason, this article aims to analyze the identified advantages and disadvantages of distance education in foreign language learning in the transition to distance education due to the pandemic COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in terms of the communication and distance education system, the statement "Distance education reduces the expenses of communication and travel" (p = .034), where females are higher than males. Based on this outcome, both groups positively agreed on the practical effect of the system as supported by the findings of Adnan (2020), Almahasees et al (2021), Lamanauskas and Makarskaite -Petkevic iene (2021), Masalimova et al (2022), andTodri et al (2021) stating that students from the university expressed that there is a reduction in the cost of traveling to university and other related expenses.…”
Section: Effects Of Different Variable On the Attitudes Of Students A...mentioning
confidence: 54%
“…The online learning-related difficulties encountered during the pandemic have been classified by Baticulon et al [ 37 ] into personal, community, technological, familiar, and institutional categories. Among these, the lack of experience with technological devices, the weakness of online teaching infrastructures, technical problems with devices or with the internet connection, and the difficulties in finding a quiet environment in which to follow the lesson represent the major challenges in both synchronous and asynchronous online education [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%